Analisis Pengaruh Variasi Arus Las TIG terhadap Karakteristik Mekanik Aluminium 6061 (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to analyze the results of Tungsten Inert Gas (TIG) welding joints made of 6061 aluminum with variations in current strength on mechanical properties. The current strength variations include 120 A, 140 A, and 160 A. The research method was conducted through laboratory testing, including impact testing, tensile testing, and microstructure testing. The results of the study indicate that variations in current strength have a significant effect on mechanical properties and weld joints. A current strength of 120 A produces a more uniform distribution of ferrite and pearlite phases in the weld zone compared to other variations. This is due to the electrical current during the welding process, which affects the heat input and cooling rate, consequently influencing the microstructure. As the current strength increases, the heat input increases, leading to changes in the material's phase composition and properties. Additionally, tensile test results showed an increase in tensile strength with increasing current strength, indicating that the welding process at higher current strengths contributes to improved material bonding and strength. Microstructure analysis revealed a more homogeneous phase distribution at higher current levels, which contributes to better weld quality and performance. This study provides valuable insights into how variations in current strength can be optimized for improved mechanical properties in TIG welding of 6061 aluminum, offering a basis for better control of welding parameters in industrial applications.